Implicit Bias and First Name Stereotypes: What are the Implications for Online Instruction? - Conaway, Wendy; Bethune, Sonja (Online Learning, 2015)
The online classroom is perceived as being a non-threatening, unbiased, safe environment due to the lack of visual cues that normally trigger hidden attitudes and biases. However, it is possible that stereotypical student names often trigger implicit bias in instructors leading to group expectations that can often manifest in a variety of ways including lack of attention or negative evaluations. In this study, we explored the relationship of underlying attitudes and biases of online instructors with respect to racially or ethnically identifiable student first names using the Brief Implicit Attitudes Test (BIAT) instrument specifically designed for this purpose. Participants included 147 online instructors with at least a Master’s degree in their given field of expertise. Using an experimental research design, we found that to a small degree, implicit bias does exist with respect to stereotypical student names. This study also found that instructors consciously believed themselves to be warm and accepting of stereotypical names. In other words, what instructors say they feel and what they really feel are distinctly different?